Screening of interferon-stimulated genes against avian reovirus infection and mechanistic exploration of the antiviral activity of IFIT5 - Wang, Sheng; Wan, Lijun; Ren, Hongyu; Xie, Zhixun; Xie, Liji; Huang, Jiaoling; Deng, Xianwen; Xie, Zhiqin; Luo, Sisi; Li, Meng; Zeng, Tingting; Zhang, Yanfang; et al. (Frontiers in Microbiology, 2022)
Avian reovirus (ARV) infection can lead to severe immunosuppression, complications, and secondary diseases, causing immense economic losses to the poultry industry. In-depth study of the mechanism by which the innate immune system combats ARV infection, especially the antiviral effect mediated by interferon, is needed to prevent and contain ARV infection. In this study, ARV strain S1133 was used to artificially infect 7-day-old specific pathogen–free chickens. The results indicated that ARV rapidly proliferated in the immune organs, including the spleen, bursa of Fabricius, and thymus. The viral load peaked early in the infection and led to varying degrees of pathological damage to tissues and organs. Real-time quantitative PCR revealed that the mRNA levels of interferon and multiple interferon-stimulated genes (ISGs) in the spleen, bursa of Fabricius, and thymus were upregulated to varying degrees in the early stage of infection. Among the ISGs, IFIT5, and Mx were the most upregulated in various tissues and organs, suggesting that they are important ISGs for host resistance to ARV infection. Further investigation of the role of IFIT5 in ARV infection showed that overexpression of the IFIT5 gene inhibited ARV replication, whereas inhibition of the endogenously expressed IFIT5 gene by siRNA promoted ARV replication. IFIT5 may be a positive feedback regulator of the innate immune signaling pathways during ARV infection and may induce IFN-α production by promoting the expression of MAD5 and MAVS to exert its antiviral effect. The results of this study help explain the innate immune regulatory mechanism of ARV infection and reveal the important role of IFIT5 in inhibiting ARV replication, which has important theoretical significance and practical application value for the prevention and control of ARV infection.